Sertoli-Leydig Cell Tumor with Concurrent Rhabdomyosarcoma: Three Case Reports and a Review of the Literature. (2nd July 2017) - Plastini, Trisha; Staddon, Arthur
Abstract : Sertoli-Leydig Cell Tumors (SLCTs) make up <1% of all ovarian tumors and are benign or malignant, androgen-secreting tumors. Rhabdomyosarcoma (RMS) is a heterogeneous group of malignant tumors that resemble developing skeletal muscle. There have been case reports of patients with concurrent SLCT and RMS with limited treatment options. We aim to demonstrate treatment strategies used in our patients, which seemed to have prolonged survival when compared to prior case reports of patients not cured by surgical resection. Herein we describe 22 cases of SLCT with RMS elements as discussed in prior case reports and three cases from the authors' institution. Of the 19 cases from prior case reports, five were lost to follow-up and two had NED after surgical intervention. Eleven patients had recurrence and were deceased within one year. Of those patients not surgically cured, only three patients were documented as living beyond two years, all of whom received chemotherapy. The three patients presented from our institution had clinical evidence of response to chemotherapy that is traditionally used for RMS. In conclusion, chemotherapy with doxorubicin and ifosfamide has activity in patients with SLCT and RMS as does salvage chemotherapy with vincristine, irinotecan, and temozolomide.